2007
DOI: 10.1002/nav.20209
|View full text |Cite
|
Sign up to set email alerts
|

Joint pricing, assortment, and inventory decisions for a retailer's product line

Abstract: Consider a set of product variants that are differentiated by some secondary attributes such as flavor, color, or size. The retailer's problem is to jointly determine the set of variants to include in her product line ("assortment"), together with their prices and inventory levels, so as to maximize her expected profit. We model the consumer choice process using a multinomial logit choice model and consider a newsvendor type inventory setting. We derive the structure of the optimal assortment for some importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 20 publications
3
49
0
2
Order By: Relevance
“…This may help explain the numerical findings of Maddah and Bish (2007), which assumes a logit demand model but uses a different approximation. They found that offering the most popular products may not be optimal, but still gives a profit very close to the optimal profit (see Tables 1-3 therein).…”
Section: The Monopoly Casementioning
confidence: 99%
See 1 more Smart Citation
“…This may help explain the numerical findings of Maddah and Bish (2007), which assumes a logit demand model but uses a different approximation. They found that offering the most popular products may not be optimal, but still gives a profit very close to the optimal profit (see Tables 1-3 therein).…”
Section: The Monopoly Casementioning
confidence: 99%
“…Using a continuous approximation, they found a similar monotonic assortment result holds in a supply chain. Maddah and Bish (2007) and Bish and Maddah (2004) studied a joint pricing, assortment, and inventory decision model for logit demand (still without demand substitution). They used numerical experiments to show that a monotonic assortment is nearly optimal and concluded that inventory cost tends to limit product variety.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…For example, Kraus and Yano (2003) considered a probabilistic choice model based on share-of-surplus model and Maddah and Bish (2007) used a multinomial logit choice model for customer choice process. Also in the literature, assortment planning problem may be considered dynamically for a multi-period horizon (e.g., Hall et al, 2010;Talebian et al, 2014, Rabbani et al, 2014 or applied in an oligopolistic environment instead of a monopolistic one (e.g.…”
Section: Literature Of Assortment Planningmentioning
confidence: 99%
“…Mahajan and van Ryzin (2001), Cachon et al (2005), Caro and Gallien (2007) and Maddah and Bish (2007) extend van Ryzin and Mahajan (1999) in various ways. Gaur and Honhon (2006) show that for a locational choice model, the products in the optimal assortment are located far from each other in the attribute space, indicating maximum differentiation, with no substitution between products in the assortment.…”
Section: Literature Reviewmentioning
confidence: 99%